2003
DOI: 10.1002/cvde.200390006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of TixSi1–xO2 Films: Precursor Chemistry Impacts Films Composition

Abstract: Thin films of composition Ti x Si 1±x O 2 were grown by low-pressure (LP) CVD on silicon (100) , as the sources of SiO 2 and TiO 2 , respectively. The substrate temperature was varied between 300 C and 535 C, and the individual precursor delivery rates ranged from 5 sccm to 100 sccm. Under these conditions, growth rates ranging from 0.6 nm min ±1 to 90.0 nm min ±1 were observed. As-deposited films were amorphous to X-rays, and cross-sectional transmission electron microscopy (TEM) images showed no composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
(17 reference statements)
0
27
1
Order By: Relevance
“…In our studies, Ti(NMe 2 ) 4 was found to be inert under 1 atm O 2 at 23 C. In the CVD reactor at 250±300 C, the reaction between Ti(NMe 2 ) 4 and O 2 was quick. The CVD reactor used was a hot-wall, horizontal apparatus [8] ( Fig.…”
mentioning
confidence: 84%
See 4 more Smart Citations
“…In our studies, Ti(NMe 2 ) 4 was found to be inert under 1 atm O 2 at 23 C. In the CVD reactor at 250±300 C, the reaction between Ti(NMe 2 ) 4 and O 2 was quick. The CVD reactor used was a hot-wall, horizontal apparatus [8] ( Fig.…”
mentioning
confidence: 84%
“…No nitride (TiN) or oxynitrided (TiO x N y ) species were observed. The work here shows that Ti(NMe 2 ) 4 is a good precursor in the CVD of TiO 2 thin films. The dielectric constant of these films is high, and these films are potential candidates for high-k applications.…”
mentioning
confidence: 95%
See 3 more Smart Citations